By applying the theory of separable ordinary differential equations we conclude that the solution of the differential equation [tex]\frac{dy}{dx} \cdot (\ln y)^{2} + y\cdot \sqrt{x} = 0[/tex] with y(0) = e is [tex]y = e^{\sqrt [3]{-2\cdot x^{\frac{3}{2} }+1}}[/tex].
In this question we must separate each variable on each side of the equivalence, integrate each side of the expression and find an explicit expression (y = f(x)) if possible.
[tex]\frac{dy}{dx} \cdot (\ln y)^{2} + y\cdot \sqrt{x} = 0[/tex]
[tex](\ln y)^{2}\,dy = -y \cdot \sqrt{x}\, dx[/tex]
[tex]-\frac{(\ln y)^{2}}{y}\, dy = \sqrt{x} \,dx[/tex]
[tex]-\int {\frac{(\ln y)^{2}}{y} } \, dy = \int {\sqrt{x}} \, dx[/tex]
If u = ㏑ y and du = dy/y, then:
[tex]-\int {u^{2}\,du } = \int {x^{\frac{1}{2} }} \, dx[/tex]
[tex]-\frac{1}{3}\cdot u^{3} = \frac{2\cdot x^{\frac{3}{2} }}{3} + C[/tex]
[tex]u^{3} = -2\cdot x^{\frac{3}{2} } + C[/tex]
[tex](\ln y)^{3} = - 2\cdot x^{\frac{3}{2} } + C[/tex]
[tex]C = (\ln e)^{3}[/tex]
[tex]C = 1[/tex]
And finally we get the explicit expression:
[tex]\ln y = \sqrt [3]{-2\cdot x^{\frac{3}{2} }+ 1}[/tex]
[tex]y = e^{\sqrt [3]{-2\cdot x^{\frac{3}{2} }+1}}[/tex]
By applying the theory of separable ordinary differential equations we conclude that the solution of the differential equation [tex]\frac{dy}{dx} \cdot (\ln y)^{2} + y\cdot \sqrt{x} = 0[/tex] with y(0) = e is [tex]y = e^{\sqrt [3]{-2\cdot x^{\frac{3}{2} }+1}}[/tex].
To learn more on ordinary differential equations: https://brainly.com/question/14620493
#SPJ1